Design of a Quasi-Yagi Antenna with Reconfigurable Frequency - Ma, Chao; Wang, Xinwei; Xue, Senyi (International Conference on Measuring Technology and Mechatronics Automation (Print), 2022)
The reconfigurable antenna can realize the functions of multiple antennas in one size structure, improve the utilization of space and reduce the mutual inteRFerence between communication systems. This paper designs a frequency reconfigurable antenna model that can switch between N78 (3.4GHz-3.6GHz) and N79 (4.8GHz-5.0GHz), aiming at the new requirements of 5G development for indoor access antennas. The quasi-yagi antenna is used when the N78 is working, and the short backshot antenna is used when the N79 is working. The reconfigurable antenna model was designed by ANSOFT HFSS and simulated. The antenna has good matching and gain after welding and assembly by simulation results. When the PIN diode is on, the antenna works in N78 band, the return loss is less than -19.58 dB, and the gain is greater than 7.44dBi. When the PIN diode is disconnected, the antenna works in N79 band, the return loss is less than -18.58dB, and the gain is greater than 9.48dBi.